2000
DOI: 10.1002/(sici)1097-461x(2000)77:2<544::aid-qua6>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of DFT and traditional ab initio methodologies on the OsO4 molecule

Abstract: ABSTRACT:The performance of different conventional ab initio methodologies and density functional procedures is compared through its application to the theoretical calculation of the bond distance and harmonic vibrational frequencies of the OsO 4 molecule. The problem of the basis set is first considered, with up to nine different basis sets being tested in calculations using the hybrid Becke3LYP density functional, and the most appropriate basis set is used in the comparison of Hartree-Fock, post-Hartree-Fock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…The ionization potential of OsO 4 is calculated to be 13.02 eV, which is very close to the experimental value 12.97 ± 0.12 eV from the mass spectrometric study . Previous theoretical work also showed that for the OsO 4 molecule the B3LYP results could give satisfactory descriptions on the geometry and vibrational frequencies, being in good agreement with CCSD(T) results and experimental data. Later in this paper we will take the dehydration of methane by OsO + as an example to further calibrate the selected method by comparison with the UCCSD(T) method.…”
Section: Computational Detailssupporting
confidence: 83%
“…The ionization potential of OsO 4 is calculated to be 13.02 eV, which is very close to the experimental value 12.97 ± 0.12 eV from the mass spectrometric study . Previous theoretical work also showed that for the OsO 4 molecule the B3LYP results could give satisfactory descriptions on the geometry and vibrational frequencies, being in good agreement with CCSD(T) results and experimental data. Later in this paper we will take the dehydration of methane by OsO + as an example to further calibrate the selected method by comparison with the UCCSD(T) method.…”
Section: Computational Detailssupporting
confidence: 83%
“…The theories tested include Hartree-Fock (HF), second-order Møller-Plesset (MP2), Slater exchange functional with the Vosko-Wilk-Nusiar correlation functional (S-VWN), B3-LYP, B3-P86, and B-VWN. Since addition of polarization functions on both metal and atoms involved in π-bonding to the metal has been shown to significantly affect the geometry of the metal, 37 they were included in the basis sets tested, which ranged from 6-31+G(d) to 6-311++G(2d,2p) (see below and Table 1). The theory/basis set that reproduced the X-ray structure of bis-(ethane-1,2dithiolato-S,S′)-zinc(II) was then employed to predict the structure of [Zn(HS) 4 ] 2and [Zn(CH 3 S) 4 ] 2-.…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the rich studies on the FeO x system, the Ru and Os analogs have received much less attention, except for the well-known tetroxides. The RuO molecule has been studied spectroscopically in the gas phase and in solid matrices. , The ground state was determined to be a 5 Δ state. ,, No spectroscopic data is available for the osmium monoxide. DFT calculations predict that a 5 Σ + state and a 3 Φ state are very close in energy. , Both the ruthenium and osmium dioxide and trioxide molecules have been observed in solid matrices. , The RuO 2 molecule was predicted to have a 1 A 1 ground state with a bond angle close to 150°. , From the isotopic frequencies for the ν 3 mode in solid neon, the upper and low limits of the RuO 2 bond angle were estimated to be 169° and 151° .…”
Section: Neutral Mononuclear Transition Metal Oxides and Dioxygen Com...mentioning
confidence: 99%